Percentagem de recombinação entre os genes C e Wₓ em milho (Zea mays L.), sob a influência do sexo, cromossomo B, knob e cromossomo 10 anormal - Ahnert, Dário; Saraiva, Luiz Sérgio (Revista Ceres, 2025)
Recombination was studied between C and Wz genes in the short arm of chromosome 9 of maize (Zea mays L.) in megasporocytes and microsporocytes as influenced by heterochromatic elements: knob, B chromosome and abnormal chromosome 10 (K10).